Budaya Patriarki sebagai Faktor Penyebab Kekerasan dalam Rumah Tangga di Indonesia : Literature Review - Dian Novita Siswanti; Eka Sufartianinsih Jafar; Muhammad Idham Zul Haq’ul; Zahwa Auralya; Muh. Ade Trio; A. Muh Raihan; Yarjuni Rahman (CV. ITTC INDONESIA, 2026)
Domestic violence (DV) remains a prevalent social issue and is closely associated with the persistence of patriarchal culture in society. The patriarchal system positions men as dominant figures within the household, while wives are placed in subordinate roles, making them more vulnerable to violence. This study aims to examine the role of patriarchy in perpetuating violence against wives. The method used is a literature review by analyzing relevant national and international journal articles. The findings indicate that patriarchy creates unequal power relations between husbands and wives, where men hold social legitimacy to control women. The construction of masculinity within patriarchal culture also shows that some men are not prepared to accept gender equality, leading to the use of violence as a means to maintain dominance. In the Indonesian context, patriarchy remains deeply rooted and is reinforced by social norms that consider domestic violence a private matter, which often hinders victims from seeking help. In conclusion, violence against wives can be understood as a manifestation of a deeply embedded patriarchal system in Indonesian society. Therefore, it is necessary to transform perspectives on gender relations by challenging male dominance and promoting equality within the household.